Analysis of Patient Satisfaction in the Emergency Department Based on the SERVPREF Model - Wemona, Fransiska Yofita Olga; Natalia, Gloria; Octaviani, Karina (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
Quality healthcare services are a crucial determinant of patient satisfaction, particularly in emergency departments where timely and accurate treatment is essential. This study investigates the influence of the five SERVPERF dimensions Tangibles, Reliability, Responsiveness, Assurance, and Empathy on patient satisfaction in the Emergency Department of Gotong Royong Hospital, Surabaya. Unlike previous studies that often generalize service quality across hospital units, this research specifically focuses on the emergency room context, where service demands and patient expectations are significantly higher. A quantitative survey approach was used, involving 150 respondents who had received ER services. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results reveal that all SERVPERF dimensions significantly affect patient satisfaction, with Empathy showing the strongest positive impact highlighting the importance of personalized care in high-pressure environments. In contrast, Reliability received the lowest rating, indicating critical areas for improvement in consistent and timely service delivery. The study contributes to the literature by offering a focused evaluation of service quality in emergency care using the SERVPERF model and provides actionable insights for hospital management to enhance patient-centered care. Regular implementation of SERVPERF-based evaluations is recommended to ensure continuous service quality improvement guided by real patient experiences.